Effect of conjugated linoleic acid on non enzymatic lipid peroxidation of mitochondria obtained from different rat tissues - Palacios, A.; Piergiacomi, V. A. (Revista Veterinaria, 2005)
The polyunsaturated fatty acid composition, chemiluminescence and peroxidizability index of mitochondria obtained from rat liver, kidney, lung and heart, were studied after oral administration of conjugated linoleic acid (CLA). After incubation of mitochondria in an ascorbate Fe++ system (120 min at 37°C), it was observed that the total counts per min/mg protein originated from light emission: chemiluminescence, was lower in liver and kidney mitochondria in the CLA group than in the control group. When peroxidized mitochondrias were compared to natives, in CLA and control groups it was observed that 18:2 n–6 decreased in all tissues used in this work. In the control group, it also decrease C20:4 n–6 and C22:6 n–6 in kidney and liver, while in lung it was affected C22:6 n–3. In CLA group, C20:4 n–6 decreased in liver and kidney, whereas in liver it also decreased C22:6 n–3. As a consequence, the peroxidizability index –a parameter based on the maximal rate of oxidation of fatty acids– showed significant changes in liver and kidney mitochondria. These changes were less pronounced in membranes derived from rats receiving CLA per os. Our results confirm and extend previous observations that indicated that CLA may act as an antioxidant, protecting membranes from deleterious effects.